Coping Strategies for Pertussis Resurgence - Xuanxuan Nian; Hongbo Liu; Mengyao Cai; Kai Duan; Xiaoming Yang (Vaccines, 2023)
Pertussis (whooping cough) is a respiratory disease caused primarily by Bordetella pertussis, a Gram-negative bacteria. Pertussis is a relatively contagious infectious disease in people of all ages, mainly affecting newborns and infants under 2 months of age. Pertussis is undergoing a resurgence despite decades of high rates of vaccination. To better cope with the challenge of pertussis resurgence, we evaluated its possible causes and potential countermeasures in the narrative review. Expanded vaccination coverage, optimized vaccination strategies, and the development of a new pertussis vaccine may contribute to the control of pertussis.